src/HOL/Typedef.thy
changeset 23710 a8ac2305eaf2
parent 23433 c2c10abd2a1e
child 24269 4b2aac7669b3
equal deleted inserted replaced
23709:fd31da8f752a 23710:a8ac2305eaf2
    27 
    27 
    28 lemma Rep_inject:
    28 lemma Rep_inject:
    29   "(Rep x = Rep y) = (x = y)"
    29   "(Rep x = Rep y) = (x = y)"
    30 proof
    30 proof
    31   assume "Rep x = Rep y"
    31   assume "Rep x = Rep y"
    32   hence "Abs (Rep x) = Abs (Rep y)" by (simp only:)
    32   then have "Abs (Rep x) = Abs (Rep y)" by (simp only:)
    33   also have "Abs (Rep x) = x" by (rule Rep_inverse)
    33   moreover have "Abs (Rep x) = x" by (rule Rep_inverse)
    34   also have "Abs (Rep y) = y" by (rule Rep_inverse)
    34   moreover have "Abs (Rep y) = y" by (rule Rep_inverse)
    35   finally show "x = y" .
    35   ultimately show "x = y" by simp
    36 next
    36 next
    37   assume "x = y"
    37   assume "x = y"
    38   thus "Rep x = Rep y" by (simp only:)
    38   thus "Rep x = Rep y" by (simp only:)
    39 qed
    39 qed
    40 
    40 
    41 lemma Abs_inject:
    41 lemma Abs_inject:
    42   assumes x: "x \<in> A" and y: "y \<in> A"
    42   assumes x: "x \<in> A" and y: "y \<in> A"
    43   shows "(Abs x = Abs y) = (x = y)"
    43   shows "(Abs x = Abs y) = (x = y)"
    44 proof
    44 proof
    45   assume "Abs x = Abs y"
    45   assume "Abs x = Abs y"
    46   hence "Rep (Abs x) = Rep (Abs y)" by (simp only:)
    46   then have "Rep (Abs x) = Rep (Abs y)" by (simp only:)
    47   also from x have "Rep (Abs x) = x" by (rule Abs_inverse)
    47   moreover from x have "Rep (Abs x) = x" by (rule Abs_inverse)
    48   also from y have "Rep (Abs y) = y" by (rule Abs_inverse)
    48   moreover from y have "Rep (Abs y) = y" by (rule Abs_inverse)
    49   finally show "x = y" .
    49   ultimately show "x = y" by simp
    50 next
    50 next
    51   assume "x = y"
    51   assume "x = y"
    52   thus "Abs x = Abs y" by (simp only:)
    52   thus "Abs x = Abs y" by (simp only:)
    53 qed
    53 qed
    54 
    54 
    74   assumes y: "y \<in> A"
    74   assumes y: "y \<in> A"
    75     and hyp: "!!x. P (Rep x)"
    75     and hyp: "!!x. P (Rep x)"
    76   shows "P y"
    76   shows "P y"
    77 proof -
    77 proof -
    78   have "P (Rep (Abs y))" by (rule hyp)
    78   have "P (Rep (Abs y))" by (rule hyp)
    79   also from y have "Rep (Abs y) = y" by (rule Abs_inverse)
    79   moreover from y have "Rep (Abs y) = y" by (rule Abs_inverse)
    80   finally show "P y" .
    80   ultimately show "P y" by simp
    81 qed
    81 qed
    82 
    82 
    83 lemma Abs_induct [induct type]:
    83 lemma Abs_induct [induct type]:
    84   assumes r: "!!y. y \<in> A ==> P (Abs y)"
    84   assumes r: "!!y. y \<in> A ==> P (Abs y)"
    85   shows "P x"
    85   shows "P x"
    86 proof -
    86 proof -
    87   have "Rep x \<in> A" by (rule Rep)
    87   have "Rep x \<in> A" by (rule Rep)
    88   hence "P (Abs (Rep x))" by (rule r)
    88   then have "P (Abs (Rep x))" by (rule r)
    89   also have "Abs (Rep x) = x" by (rule Rep_inverse)
    89   moreover have "Abs (Rep x) = x" by (rule Rep_inverse)
    90   finally show "P x" .
    90   ultimately show "P x" by simp
    91 qed
    91 qed
    92 
    92 
    93 lemma Rep_range:
    93 lemma Rep_range:
    94 assumes "type_definition Rep Abs A"
    94 assumes "type_definition Rep Abs A"
    95 shows "range Rep = A"
    95 shows "range Rep = A"